Studi Interpretatif Fenomenologi: Penggunaan Strategi Mnemonik sebagai Sarana Pembelajaran Bahasa Inggris Perguruan Tinggi - Octa Pratama Putra (Journal on Education, 2024)
For English teachers, there are several variations in delivering the idea of teaching English. These variations aim to prevent boredom in learning for students and to optimize teaching and learning activities. The purpose of this research is to reveal qualitative reasons for five selected-English lecturers when teaching English by using mnemonic strategies at Bina Sarana Informatika University, Jakarta. The method in this research is using the Interpretative Phenomenology Study; in which the author interviews in detail to reveal the exploration of an effort by the lecturer used when teaching English in certain English topic. After using the mnemonic strategy, the results stated that, there were five results, they are: 1. Facilitating Memory in Learning. 2. Increasing Memory. 3. Illustrating a Memory. 4. Facilitating Teaching and Learning Activities. and 5. Creating the Own in the Application of Mnemonic Strategies by Acronyms. As the additional result, students’ attraction and interest will increase. Then, this will also lead to an increase in learning outcomes, absolutely to their grades or score.